KINERJA KEUANGAN DAN PENGAKUAN PASAR SEBAGAI PREDIKTOR RETURN SAHAM (STUDI PADA PERUSAHAAN INDEKS LQ 45) - Alvionita Sutrisno, Elizabeth Ayu; Kesuma, Ketut Wijaya (E-Jurnal Manajemen, 2016)
Return is the main reason for investors to invest. Investors always want optimal return, therefore it needs to analyze the development of the company's financial reports before making a decision. The company's financial reports will provide an overviewfor investor show the company's condition. This study aim to determine the effect of the CR, DER, NPM, TATO, PER and MBV towards the stock return on firms that included in LQ 45 index in 2012-2014. The study examines the corporate that joined in LQ 45 index during 2012-2014. The number of samples was 23 by using purposive sampling method with multiple linear regression analysis as the data analysis technique. These results indicate that current ratio, debt to equity ratio, net profit margin, total assets turnover and price earning ratio positive insignificant effect on stock return. Market to book value negative significant on stock return.
Keywords: stock return, financial performance, market ratio